A Note on Kaehler Manifolds (European Journal of Pure and Applied Mathematics, 2010)
The object of the present paper is to prove that in a Kaehler manifold of dimension n ≥ 4, div R = 0 and div C = 0 are equivalent, where ’div’ denotes divergence and R and C denote the curvature tensor and Weyl conformal curvature tensor, respectively.